Differentiation between myopericarditis and acute myocardial infarction on presentation in the emergency department using the admission C-reactive protein to troponin ratio. - Simcha R Meisel; Hamuda Nashed; Randa Natour; Rami Abu Fanne; Majdi Saada; Naama Amsalem; Carmel Levin; Ofer Kobo; Aaron Frimerman; Yaniv Levi; Jameel Mohsen; Avraham Shotan; et al. (PLoS ONE, 2021)
Background The treatment of myopericarditis is different than that of acute myocardial infarction (AMI). However, since their clinical presentation is frequently similar it may be difficult to distinguish between these entities despite a disparate underlying pathogenesis. Myopericarditis is primarily an inflammatory disease associated with high C-reactive protein (CRP) and relatively low elevated troponin concentrations, while AMI is characterized by the opposite. We hypothesized that evaluation of the CRP/troponin ratio on presentation to the emergency department could improve the differentiation between these two related clinical entities whose therapy is different. Such differentiation should facilitate triage to appropriate and expeditious therapy. Methods We evaluated the CRP/troponin ratio on presentation among patients consecutively included in a large single center registry that included 1898 consecutive patients comprising 1025 ST-elevation myocardial infarction (STEMI) patients, 518 Non-STEMI (NSTEMI) patients, and 355 patients diagnosed on discharge as myopericarditis. CRP and troponin were sampled on admission in all patients and their ratio was assessed against discharge diagnosis. ROC analysis of the CRP/troponin ratios evaluated the diagnostic accuracy of myopericarditis against all AMI, STEMI, and NSTEMI patients. Results Median admission CRP/troponin ratios were 84, 65, and 436 mg×ml/liter×ng in STEMI, NSTEMI and myopericarditis groups, respectively (p<0.001) demonstrating good differentiating capability. The Receiver-operator-curve of admission CRP/troponin ratio for diagnosis of myopericarditis against all AMI, STEMI, and NSTEMI patients yielded an area-under-the curve of 0.74, 0.73, and 0.765, respectively. CRP/troponin ratio>500 resulted in specificity exceeding 85%, and for a ratio>1000, specificity>92%. Conclusion The CRP/troponin ratio can serve as an effective tool to differentiate between myopericarditis and AMI. In the appropriate clinical context, the CRP/troponin ratio may preclude further evaluation.